Taiwan's Experience in Hospital Preparedness and Response for Emerging Infectious Diseases - Kao, Hui-Yun (Health Secur, 2017)
The Communicable Disease Control Medical Network (CDCMN), established in 2003 after the SARS outbreak in Taiwan, has undergone several phases of modification in structure and activation. The main organizing principles of the CDCMN are centralized isolation of patients with severe highly infectious diseases and centralization of medical resources, as well as a network of designated regional hospitals like those in other countries. The CDCMN is made up of a command system, responding hospitals, and supporting hospitals. It was tested and activated in response to the H1N1 influenza pandemic in 2009-10 and the Ebola outbreak in West Africa in 2014-2016, and it demonstrated high-level functioning and robust capacity. In this article, the history, structure, and operation of the CDCMN is introduced globally for the first time, and the advantages and challenges of this system are discussed. The Taiwanese experience shows an example of a collaboration between the public health system and the medical system that may help other public health authorities plan management and hospital preparedness for highly infectious diseases.